Monetary policy and rejections of the expectations hypothesis - Federico Ravenna; Juha Seppälä (Bank of Finland, 2006)
We study the rejection of the expectations hypothesis within a New Keynesian business cycle model.Earlier research has shown that the Lucas general equilibrium asset pricing model can account for neither sign nor magnitude of average risk premia in forward prices, and is unable to explain rejection of the expectations hypothesis.We show that a New Keynesian model with habitformation preferences and a monetary policy feedback rule produces an upwardsloping average term structure of interest rates, procyclical interest rates, and countercyclical term spreads.In the model, as in U.S. data, inverted term structure predicts recessions.Most importantly, a New Keynesian model is able to account for rejections of the expectations hypothesis.Contrary to earlier work, we identify systematic monetary policy as a key factor behind this result.Rejection of the expectation hypothesis can be entirely explained by the volatility of just two real shocks which affect technology and preferences.
URN:NBN:fi:bof-20140807467
Keywords: E43; E44; G12; 330; term structure of interest rates; monetary policy; sticky prices; habit formation; expectations hypothesis